Peningkatan Kinerja Pegawai melalui Kenyamanan Lingkungan, Kepemimpinan, dan Manajemen Waktu: Studi di Pemerintah Provinsi Kepulauan X dengan Mediasi Keterlibatan Pegawai - Wazdy, Nadhira Alya; Setyawan, Agustinus; Sudhartio, Lily (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: The purpose of this finding is to interpret the influence of employee comfort, leadership, time management, and employee involvement on employee performance. Method: This research uses a quantitative approach with a survey. Finding: These findings interpret that the work environment has a significant positive impact on employee engagement, but does not have a significant effect on employee performance. Meanwhile, leadership and time management have a significant positive impact on employee engagement and employee performance. Meanwhile, employee involvement itself provides a significant positive relationship to employee performance. Theoretical contribution/Originality: These findings provide a deep understanding of the importance of good and quality leadership in increasing employee engagement and performance in government and corporate environments. Practitioner/Policy implication: aspects that can have an impact on an employee's performance must always be considered and evaluated regularly so that employee productivity at work remains constant and even increases. Organizations and companies must also implement optimal human resource management to maintain employee loyalty and integrity. Research limitation: Research limitations only focus on the object of research, namely Civil Servants in the Riau Islands Provincial Government.